RBPMS2 can inhibit the NLRP3 / caspase-1 / GSDMD signaling pathway to resist pyroptosis in gastric cancer cells - Nailin Zhang; Lina Yan; Hua Cao; Nana Zhang; Tong Zhang; Shengjiang Guan; Qiquan Liu (Scientific Reports)
Abstract Gastric cancer (GC) is one of the most common malignancies worldwide, and its development is closely associated with the abnormal expression of numerous genes. RNA - binding protein with multiple splicing 2 (RBPMS2), a member of the RNA - binding protein family, has recently been found to be abnormally activated in GC cells. Meanwhile, pyroptosis, a form of programmed cell death, is related to tumorigenesis, development, and immune responses.This study investigated the role of the RNA - binding protein RBPMS2 in GC. It revealed the high expression of RBPMS2 in GC cells and its association with poor prognosis. RBPMS2 promoted the proliferation, invasion, and migration of GC cells while inhibiting pyroptosis by suppressing the NLR family pyrin domain containing 3 (NLRP3)/caspase − 1/gasdermin (DGSDMD) signaling pathway. Knocking out RBPMS2 activated pyroptosis, leading to cell membrane damage and increased expression of pyroptosis - related proteins. The NLRP3 inhibitor MCC950 reversed these effects, confirming the involvement of this pathway. These findings suggest that RBPMS2 may be a potential therapeutic target for inducing pyroptosis in gastric cancer cells, providing novel insights into treatment strategies for gastric cancer.